Monte Carlo radiative transfer for the nebular phase of type Ia supernovae - Shingles, Luke J.; Kromer, Markus; Röpke, Friedrich (Monthly notices of the Royal Astronomical Society, 2020)
ABSTRACT. We extend the range of validity of the artis 3D radiative transfer code up to hundreds of days after explosion, when Type Ia supernovae (SNe Ia) are
Advance access publication 2019 December 31
Gesehen am 17.02.2020